2017
DOI: 10.19110/2221-1381-2017-9-30-33
|View full text |Cite
|
Sign up to set email alerts
|

Identification of elastic symmetry elements in anisotropic rock samples by x-ray tomography

Abstract: Ìåòîäîì ðåíòãåíîâñêîé òîìîãðàôèè èññëåäîâàíû äâà îáðàçöà ïåñ÷àíèêîâ, ðàíåå èçó÷åííûõ ìåòîäîì àêóñòîïî-ëÿðèñêîïèè ñ îïðåäåëåíèåì òèïà óïðóãîé ñèììåòðèè è ïðîñòðàíñòâåííîãî ïîëîaeåíèÿ ýëåìåíòîâ óïðóãîé ñèììåòðèè ïîðîä. Ñðàâíåíèå ðåçóëüòàòîâ èññëåäîâàíèÿ ïîêàçàëî ïðîñòðàíñòâåííîå ñîâïàäåíèå ðàíåå óñòàíîâëåííûõ ýëåìåíòîâ óïðóãîé ñèììåòðèè ñ ñèñòåìíîé îðãàíèçàöèåé íåîäíîðîäíîñòåé (òåêñòóðà, ïîðèñòîñòü, ìèêðîòðåùèíîâàòîñòü), êîòî-ðûå ëåãêî âèçóàëèçèðóþòñÿ íà ðåíòãåíîâñêèõ òîìîãðàììàõ.Êëþ÷åâûå ñëîâà: ðåíòãåíîâñêàÿ òî… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Apparently, this method can also be efficiently used in the study of ore deposits, since it allows the transition from a two-dimensional image of textural and structural features of rocks and ores (and distribution of the components of interest) to three-dimensional one [10], thus leading to gaining important information about the mechanism of ore formation [11]. Recently it was shown that the results of CT allow locating the spatial position of small cracks (the main cause of elastic anisotropy) in samples of anisotropic sandstones [12].…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, this method can also be efficiently used in the study of ore deposits, since it allows the transition from a two-dimensional image of textural and structural features of rocks and ores (and distribution of the components of interest) to three-dimensional one [10], thus leading to gaining important information about the mechanism of ore formation [11]. Recently it was shown that the results of CT allow locating the spatial position of small cracks (the main cause of elastic anisotropy) in samples of anisotropic sandstones [12].…”
Section: Introductionmentioning
confidence: 99%